Intranasal Delivery of BACE1 siRNA and Berberine via Engineered Stem Cell Exosomes for the Treatment of Alzheimer’s Disease - Sun C; Sha S; Shan Y; Gao X; Li L; Xing C; Guo Z; Du H (International Journal of Nanomedicine)
Chunbin Sun,1,* Shuang Sha,1,* Yubang Shan,1 Xiaoyu Gao,1 Liang Li,1 Cencan Xing,1,2,* Zhongbao Guo,3,* Hongwu Du1,2,* 1School of Chemistry and Biological Engineering, University of Science and Technology Beijing, Beijing, 100083, People’s Republic of China; 2Daxing Research Institute, University of Science and Technology Beijing, Beijing, 100083, People’s Republic of China; 3China Testing & Certification International Group Co., Ltd, Beijing, 100024, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongwu Du, School of Chemistry and Biological Engineering, University of Science and Technology Beijing, Beijing, 100083, People’s Republic of China, Email hongwudu@ustb.edu.cn Zhongbao Guo, China Testing & Certification International Group Co., Ltd, Beijing, 100024, People’s Republic of China, Email gzb@ctc.ac.cnIntroduction: Alzheimer’s disease (AD) is a common progressive and irreversible neurodegenerative disease. AD accounts for 60%– 70% of all dementia cases, ranking as the seventh leading cause of death globally. Human umbilical cord mesenchymal stem cells (hUC-MSCs) characterized by their abundant availability and low immunogenicity, have demonstrated significant therapeutic potential for AD in both preclinical studies and clinical trials. The use of exosomes can help mitigate the issues associated with cellular therapies. However, the clinical application of hUC-MSCs remains challenging due to their inability to effectively traverse the blood-brain barrier (BBB) and reach pathological sites. Therapeutic strategies utilizing exosomes derived from hUC-MSCs (Exos) have emerged as an effective approach for AD intervention.Methods: Here, we used ultrasound to construct multifunctional Exos (MsEVB@R/siRNA) for AD therapy. We obtained small interfering RNA for β-site precursor protein lyase-1 (BACE1 siRNA) and berberine for co-delivery into the brain. Berberine, a classical anti-inflammatory agent, effectively alleviates neuroinflammation in AD pathogenesis. BACE1 serves as the pivotal cleavage enzyme in amyloid β-protein (Aβ) formation, where silencing BACE1 synthesis through BACE1 siRNA significantly reduces Aβ production. In a 5xFAD mouse model, Exos selectively targeted microglial and neuronal cells after nasal delivery under the action of neural cell-targeting peptide rabies virus glycoprotein 29 (RVG29).Results: BACE1 siRNA and berberine (BBR) loading enhanced the effectiveness of Exos in improving cognitive function, promoting nerve repair and regeneration, reducing inflammatory cytokine expression, and suppressing glial responses. BACE1 siRNA release was confirmed to reduce BACE1 expression and Aβ deposition. Concurrently, berberine effectively suppressed the release of inflammatory factors, thereby reducing neuroinflammation.Conclusion: In conclusion, the nasal delivery of engineered exosomes is a potentially effective method for treating AD. Keywords: Alzheimer’s disease, engineering exosomes, intranasal delivery